The crank of partitions mod 13 - Göksal, Bilgici (Springer Science and Business Media LLC, 2012)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: Partitions; congruences and congruential restrictions; crank; rank; partition